An Empirical Study on Consumer Buying Behavior in Online Shopping in Bangalore City (International Journal of Food and Nutritional Sciences, 2022)
Online shopping is growing rapidly in India, predominantly driven by tremendous and substantial divulgatory activities among millennial consumers. Online shopping is becoming more popular and attracts significant attention because it has excellent potential for both consumers and vendors. The convenience of online shopping makes it more successful and makes it an emerging trend among consumers. When all the companies are striving against one another, certain factors influence the behavior of customers. Out of 260 circulated questionnaires, 212 were given back as complete and adequate to use in the analysis of data. Convenience sampling method was used to collect the data and the data was analyzed by using the SPSS Software 28. The results revealed that the independent variables Perceived Benefits, Domain Specific Innovativeness and Shopping Orientations are positively related with dependent variable, Consumer Buying Behavior. Results provided in this research could be employed as reference information for online shopping consumers.